2012
DOI: 10.1371/journal.pone.0046892
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-Catenin Pathway Cross-Talks with STAT3 Signaling to Regulate Survival of Retinal Pigment Epithelium Cells

Abstract: Wnt/β-catenin signaling is an essential pathway that regulates numerous cellular processes, including cell survival. The molecular mechanisms contributing to pro-survival Wnt signaling are mostly unknown. Signal transducer and activator of transcription proteins (STATs) are a well-described family of transcription factors. STAT3 induces expression of anti-apoptotic genes in many tissues and is a downstream mediator of protective growth factors and cytokines. In this study, we investigated whether pro-survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 54 publications
5
66
0
Order By: Relevance
“…We identified STAT3 as a necessary component in TLR3 induced protection during injury. To our knowledge, this is the first study to link Stat3 protection to an immune mediated protective response in neurons, and is supported by a vast literature on the protective role of Stat3 signaling in neurodegeneration and retinal health (Zhang et al, 2008; Fragoso et al, 2012; Patel and Hackam, 2012). We observed that neither TLR3 activation nor oxidative stress induced significant increases in Stat3 activation; however, the combination of these two pathways triggers increased Stat3 signaling.…”
Section: Discussionmentioning
confidence: 55%
“…We identified STAT3 as a necessary component in TLR3 induced protection during injury. To our knowledge, this is the first study to link Stat3 protection to an immune mediated protective response in neurons, and is supported by a vast literature on the protective role of Stat3 signaling in neurodegeneration and retinal health (Zhang et al, 2008; Fragoso et al, 2012; Patel and Hackam, 2012). We observed that neither TLR3 activation nor oxidative stress induced significant increases in Stat3 activation; however, the combination of these two pathways triggers increased Stat3 signaling.…”
Section: Discussionmentioning
confidence: 55%
“…The transcription factor Stat3 plays a role in axonal regrowth (Pellegrino and Habecker, 2013, Qin et al, 2013) and Stat3 is induced by Wnt3a and contributes to Wnt3a-mediated survival of multiple retinal cell types (Fragoso et al, 2012, Patel and Hackam, 2012, 2014b, Patel et al, 2015b). To determine whether the Stat3 pathway contributes to Wnt3a-induced RGC survival and axonal growth after injury, we first tested whether Wnt3a activates Stat3 signaling in the retina.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt3a may also indirectly promote regeneration by inducing expression of its target genes such as pro-regeneration molecules STAT3, CNTF and neurotrophins (Fragoso et al, 2012, Yi et al, 2012a, Patel et al, 2015b). Furthermore, Wnt signaling could be enhanced through endogenous regulation of Wnt antagonists, such as through microRNA-431-mediated targeting of the Wnt inhibitor Kremen1, as observed with axon regeneration of sensory neurons (Wu and Murashov, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To activate Wnt/β-catenin signaling pathway, BMSCs were treated with 20 µM BIO (Sigma) for 24 h [36,37]. …”
Section: Methodsmentioning
confidence: 99%